Stoic Resilience, Moral Autonomy, and The Dichotomy of Control Parallel Tawakkul, Sabr, and Ikhtiyar - Kuznetsov, Michael Yurievich (el Harakah: Jurnal Budaya Islam, 2025)
The need to uncover how Islamic intellectual and spiritual traditions have historically interacted with non-Islamic systems of thought to develop a distinct ethical psychology grounded in revelation. Despite the Qur’an and Islamic scholarship offering profound frameworks for emotional resilience—such as tawakkul, ṣabr, and riḍā bi’l-qaḍā’—the specific historical reception of Epictetus’s Stoic ethics within Islamic thought remains largely underexplored. This research addresses that gap by systematically tracing how Muslim philosophers and theologians received, adapted, or Islamized Epictetus’s ideas of self-mastery and rational discipline. Its novelty lies in integrating historical-philosophical analysis with contemporary Islamic psychology, thereby offering a new interpretive bridge between Stoic practical ethics and Qur’anic models of inner reform and mental resilience. This article examines Epictetus’ Stoicism as a timeless practical philosophy of moral freedom and resilience, with particular emphasis on its striking structural parallels and historical reception within Islamic ethical thought. The central purpose is to demonstrate that the famous Stoic “dichotomy of control” (what is eph’ hēmin and what is not), the discipline of assent, and the concept of the inner citadel find close equivalents in core Islamic concepts of ikhtiyār (sphere of moral choice), tawakkul (trust in divine decree), sabr (patient perseverance), and riḍā bi’l-qaḍāʾ (contentment with God’s ordainment). Using a comparative textual and historical-critical method, the study analyses primary sources from Epictetus (Discourses and Enchiridion) alongside Muslim thinkers who explicitly or implicitly engaged Stoic ideas. The analysis reveals that Stoic therapeutic techniques entered the Islamic tradition through the Graeco-Arabic translation movement and were consciously adapted to enrich Qurʾānic-Sufi ethics of self-mastery and spiritual resilience. The scholarly contribution of this study goes beyond general “Stoicism–Islam” comparisons. It demonstrates how Epictetus’ practical methods were integrated into Islamic moral psychology. This approach provides contemporary Muslim scholarship with a pre-modern, cross-cultural resource to address mental health, ethical decision-making amid uncertainty, and cosmopolitan responsibility in a globalized world. Kebutuhan untuk mengungkap bagaimana tradisi intelektual dan spiritual Islam secara historis berinteraksi dengan sistem pemikiran non-Islam guna mengembangkan psikologi etis yang khas dan berlandaskan wahyu masih sangat penting. Meskipun Al-Qur’an dan khazanah keilmuan Islam telah menawarkan kerangka mendalam bagi ketangguhan emosional—seperti tawakkul, ṣabr, dan riḍā bi’l-qaḍā’—penerimaan historis terhadap etika Stoa Epictetus dalam pemikiran Islam masih jarang dikaji secara mendalam. Penelitian ini berupaya mengisi kekosongan tersebut dengan menelusuri secara sistematis bagaimana para filsuf dan teolog Muslim menerima, mengadaptasi, atau mengislamkan gagasan Epictetus tentang penguasaan diri dan disiplin rasional. Kebaruan penelitian ini terletak pada integrasi antara analisis historis-filosofis dan psikologi Islam kontemporer, sehingga menghadirkan jembatan interpretatif baru antara etika praktis Stoa dan model Qur’ani tentang reformasi batin serta ketangguhan mental. Artikel ini mengkaji Stoikisme Epiktetus sebagai filosofi praktis kebebasan moral dan ketahanan yang abadi, dengan penekanan khusus pada kesejajaran strukturalnya yang mencolok dan penerimaan historisnya dalam pemikiran etika Islam. Tujuan utamanya adalah untuk menunjukkan bahwa "dikotomi kendali" Stoik yang terkenal (apa yang eph’ hēmin dan apa yang tidak), disiplin persetujuan (assent), dan konsep benteng batin memiliki padanan yang erat dalam konsep inti Islam: ikhtiyār (lingkup pilihan moral), tawakkul (kepercayaan pada ketetapan ilahi), sabr (ketekunan yang sabar), dan riḍā bi’l-qaḍāʾ (kerelaan terhadap ketetapan Tuhan). Dengan menggunakan metode komparatif tekstual dan historis-kritis, penelitian ini menganalisis sumber-sumber primer dari Epiktetus (Discourses dan Enchiridion) di samping para pemikir Muslim yang secara eksplisit atau implisit melibatkan ide-ide Stoik. Analisis mengungkapkan bahwa teknik terapeutik Stoik memasuki tradisi Islam melalui gerakan penerjemahan Yunani-Arab dan secara sadar diadaptasi untuk memperkaya etika Al-Qur'an-Sufi tentang penguasaan diri dan ketahanan spiritual. Kontribusi ilmiah dari penelitian ini melampaui perbandingan umum antara “Stoisime dan Islam.” Studi ini menunjukkan bagaimana metode praktis Epictetus diintegrasikan ke dalam psikologi moral Islam. Pendekatan ini memberikan khazanah keilmuan Islam kontemporer sumber daya lintas budaya dari masa pra-modern untuk menghadapi isu kesehatan mental, pengambilan keputusan etis di tengah ketidakpastian, serta tanggung jawab kosmopolitan dalam dunia yang semakin mengglobal.